2016
DOI: 10.1002/pdi.2018
|View full text |Cite
|
Sign up to set email alerts
|

Addition of SGLT2 inhibitor to GLP-1 agonist therapy in people with type 2 diabetes and suboptimal glycaemic control

Abstract: This study aimed to observe the effect of the novel combination of dual add‐on therapy of a sodium‐glucose co‐transporter‐2 (SGLT2) inhibitor to a glucagon‐like peptide‐1 receptor agonist (GLP‐1 RA) on glycaemic control and weight in patients with suboptimal diabetes control who are already on antidiabetic treatment after failure of a GLP‐1 RA therapy alone. We conducted a retrospective observational case note review of patients who had a minimum of 12 weeks’ treatment with a GLP‐1 RA added onto their previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…A randomized, placebo-controlled study combining exenatide QW and dapagliflozin in participants who were obese without diabetes reported significant weight loss, BP reduction, and glucose normalization without unexpected AEs (22). Findings from real-world observational and retrospective analyses further support the use of these two drug classes in combination (23)(24)(25)(26)(27)(28). Although having a different design to DURATION-8, the recent Assessment of Weekly Administration of LY2189265 (dulaglutide) in Diabetes-10 (AWARD-10) trial among patients with inadequately controlled type 2 diabetes receiving an SGLT2 inhibitor with or without metformin demonstrated improved glycemic control with add-on dulaglutide therapy versus placebo (29).…”
Section: Discussionmentioning
confidence: 94%
“…A randomized, placebo-controlled study combining exenatide QW and dapagliflozin in participants who were obese without diabetes reported significant weight loss, BP reduction, and glucose normalization without unexpected AEs (22). Findings from real-world observational and retrospective analyses further support the use of these two drug classes in combination (23)(24)(25)(26)(27)(28). Although having a different design to DURATION-8, the recent Assessment of Weekly Administration of LY2189265 (dulaglutide) in Diabetes-10 (AWARD-10) trial among patients with inadequately controlled type 2 diabetes receiving an SGLT2 inhibitor with or without metformin demonstrated improved glycemic control with add-on dulaglutide therapy versus placebo (29).…”
Section: Discussionmentioning
confidence: 94%
“…Further study is required to evaluate the mode of action of tofogliflozin in lipid metabolism. Recent small retrospective cohort studies showed clinical benefits, including weight loss and diabetes improvement, with the combination of GLP‐1 receptor agonists and SGLT2 inhibitors. The combination of dapagliflozin with GLP‐1 receptor agonist was reported to be generally well tolerated, and significantly reduced the mean HbA1c levels and bodyweight in patients with type 2 diabetes mellitus, with a significant decrease in blood pressure, a significant increase of TC and HDL‐C, and a decrease of TG Deo et al reported a retrospective study of combination therapy of GLP‐1 receptor agonists with SGLT2 inhibitors for the management of diabesity, resulting in significant improvements in clinical parameters, such as bodyweight loss (3.1 kg), HbA1c reduction (1.1%), lower BMI (−1.1 kg/m 2 ) and insulin dose reduction (6.8 units), but the combination therapy was not associated with a reduction in blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…This study documented a very modest HbA1c reduction. In another small retrospective study ( n = 14) from the United Kingdom sequential addition of GLP-1RA followed by SGLT-2 inhibitor was analyzed [ 10 ]. On addition of a GLP1 RA, HbA1c came down by 8 mmol/mol (0.7%), with an associated 4.9 kg weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…The recent DURATION 8 study, testing the above rationale, demonstrated an additive effect on weight and systolic blood pressure reduction but not HbA1c reduction when exenatide LAR, a GLP-1 RA and dapagliflozin, a SGLT2i were used in combination as a co-initiation strategy [ 7 , 8 ]. However multiple observational studies suggested that GLP-1 RA and SGLT2i are additive from a metabolic perspective as well, when SGLT2i was added to GLP-1 RA (sequential initiation instead of co-initiation) [ 9 , 10 ]. This is contrary to a real world scenario where usually injectable are added only when oral drugs fail.…”
Section: Introductionmentioning
confidence: 99%